Chemical Synthesis of a Glycopeptide Derived from Skp1 for Probing Protein Specific Glycosylation. Issue 33 (15th July 2015) - Chinoy, Zoeisha S.; Schafer, Christopher M.; West, Christopher M.; Boons, Geert‐Jan
Abstract Skp1 is a cytoplasmic and nuclear protein, best known as an adaptor of the SCF family of E3‐ubiquitin ligases that label proteins for their degradation. Skp1 in Dictyostelium is posttranslationally modified on a specific hydroxyproline (Hyp) residue by a pentasaccharide, which consists of a Fucα1, 2‐Galβ‐1, 3‐GlcNAcα core, decorated with two α‐linked Gal residues. A glycopeptide derived form Skp1 was prepared to characterize the α‐galactosyltransferase (AgtA) that mediates the addition of the α‐Gal moieties, and to develop antibodies suitable for tracking the trisaccharide isoform of Skp1 in cells. A strategy was developed for the synthesis of the core trisaccharide‐Hyp based on the use of 2‐naphthylmethyl (Nap) ethers as permanent protecting groups to allow late stage installation of the Hyp moiety. Tuning of glycosyl donor and acceptor reactivities was critical for achieving high yields and anomeric selectivities of glycosylations. The trisaccharide‐Hyp moiety was employed for the preparation of the glycopeptide using microwave‐assisted solid phase peptide synthesis. Enzyme kinetic studies revealed that trisaccharide‐Hyp and trisaccharide‐peptide are poorly recognized by AgtA, indicating the importance of context provided by the native Skp1 protein for engagement with the active site. The trisaccharide‐peptide was a potent immunogen capable of generating a rabbit antiserum that was highly selective toward the trisaccharide isoform of full‐length Skp1.